2020
DOI: 10.1212/nxi.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

Age-related visual dynamics in HIV-infected adults with cognitive impairment

Abstract: ObjectiveTo investigate whether aging differentially affects neural activity serving visuospatial processing in a large functional neuroimaging study of HIV-infected participants and to determine whether such aging effects are attributable to differences in the duration of HIV infection.MethodsA total of 170 participants, including 93 uninfected controls and 77 HIV-infected participants, underwent neuropsychological assessment followed by neuroimaging with magnetoencephalography (MEG). Time-frequency analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Perhaps most relevant to the current study, Wiesman and colleagues found that some occipital neural responses during a visual processing task distinguished PWH based on their impairment status and were significantly correlated with behavioral performance [37] . A more recent study using a similar visual processing task extended these findings by showing that such neural dynamics were differentially affected by age in PWH and controls [38] . Finally, a multimodal neuroimaging (MEG and MRI) study suggested that at least some aberrant oscillatory neural responses in PWH may be associated with reductions in local grey matter volume [39] .…”
Section: Introductionmentioning
confidence: 69%
“…Perhaps most relevant to the current study, Wiesman and colleagues found that some occipital neural responses during a visual processing task distinguished PWH based on their impairment status and were significantly correlated with behavioral performance [37] . A more recent study using a similar visual processing task extended these findings by showing that such neural dynamics were differentially affected by age in PWH and controls [38] . Finally, a multimodal neuroimaging (MEG and MRI) study suggested that at least some aberrant oscillatory neural responses in PWH may be associated with reductions in local grey matter volume [39] .…”
Section: Introductionmentioning
confidence: 69%
“…EEG is non-invasive and relatively inexpensive, so could be feasible even in resource-poor settings. There is evidence, albeit mainly from small samples, that measures from EEG (or the related technique of magnetoencephalography (MEG)) can distinguish HIV+ from HIV-groups, as well as groups with and without HIV-associated neurocognitive disorders (HAND) [16][17][18][19]. However, little work has been done to identify EEG markers associated with individual differences in cognitive performance amongst people with HIV; such markers could shed light on the underlying pathophysiology of cognitive impairment and serve as candidates for diagnostic or interventionmonitoring purposes at the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…EEG is non-invasive and relatively inexpensive, so could be made widely available, even in resource-poor settings, yet there has been surprisingly little application of these methods in HIV (Fernández-Cruz & Fellows, 2017). There is evidence, albeit mainly from small sample studies, that EEG/MEG measures can distinguish people with HIV infection from HIV-controls, and HIV+ individuals with and without HIV-associated neurocognitive disorders (HAND) (Fernández-Cruz & Fellows, 2017; Groff et al, 2020; Lew et al, 2018; Wiesman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%